Effects of oily fish and its fatty acid intake on non-alcoholic fatty liver disease development among South Korean adults - Tan, Li-Juan; Shin, Sangah (Frontiers in Nutrition, 2022)
Background: The benefits of fish fatty acid intake for non-alcoholic fatty liver disease (NAFLD) are rarely reported, although a previous study assessed the relationship between oily fish consumption and the prevalence of NAFLD. Aims: We investigated whether oily fish and fish-based monounsaturated fatty acids, polyunsaturated fatty acids, and omega-3 fatty acids affect the development of NAFLD in South Korean adults. Methods: In this large-scale cohort study, 44,139 participants of the Health Examinees study were selected for analysis after 5 years of follow-up. NAFLD is diagnosed with a non-invasive index, the fatty liver index. Using multivariable Cox proportional hazards models, adjusted for age, body mass index, total energy intake, education, physical activity, smoking status, and drinking (alcohol) status, we calculated the hazard ratios and 95% confidence intervals. Results: For men, NAFLD had no statistically significant associations with quartiles of total oily fish or its fatty acid intake. However, among women, an inverse association was observed (all P for trend < 0.05). Regarding the standard deviation increment of total oily fish or its fatty acid intake by one, all fatty acids from oily fish showed inverse associations for NAFLD in both men and women. After stratified analyses, we found that drinking status and menopause status were independent risk factors for NAFLD. Conclusion: Oily fish and its fatty acid intake showed a preventative benefit for NAFLD , especially in South Korean women.